Molecular Pathology and CXCR4 Expression in Surgically Excised Retinal Hemangioblastomas Associated with von Hippel-Lindau Disease - Liang, Xiaoling (2006)
PURPOSE: The surgical excision of retinal vascular lesions including hemangioblastomas is rarely practiced. This study investigates the pathological characteristics of 4 patients (3 with von Hippel-Lindau [VHL] disease and 1 with a vasoproliferative retinal tumor) who underwent ocular tumor resection, von Hippel-Lindau is an autosomal dominant disease caused by a defect of the VHL tumor suppressor gene. The VHL protein is required for oxygen-dependent degradation of hypoxia-inducible factor 1α. This factor regulates vascular endothelial growth factor (VEGF) and the chemokine receptor CXCR4. Retinal hemangioblastoma is the most common tumor observed in VHL disease. We investigated the expression of CXCR4; its ligand, CXCL12/SDF-1α; VEGF; and the VHL gene in VHL disease–associated retinal hemangioblastomas. DESIGN: Interventional case series with immunohistological and molecular pathological analyses. PARTICIPANTS: Immunohistochemistry and molecular pathology of the surgically excised retinal lesions were performed. INTERVENTION: Large retinal hemangioblastomas (1–3 disc diameters) and vasoproliferative tumors were resected surgically after laser photocoagulation in 4 patients. The excised tissues were snap frozen and evaluated by histology. Molecular pathology was performed for the VHL gene, and immunohistochemistry and molecular detection (reverse transcription polymerase chain reaction) were carried out for VEGF, CXCR4, and CXCL12. MAIN OUTCOME MEASURES: Evaluation of clinical presentations and molecular pathology of the excised retinal lesions. RESULTS: Large retinal hemangioblastomas were resected successfully from the 3 VHL cases. Postoperatively, all patients were stable. Molecular analyses disclosed the loss of heterozygosity at the VHL allele locus in the VHL retinal hemangioblastomas but not in the vasoproliferative tumor. High levels of transcript and protein were found for VEGF and CXCR4, whereas low levels of CXCL12 mRNA were expressed in the retinal hemangioblastomas associated with VHL disease. In contrast, very low levels of VEGF and CXCR4 mRNA were detected in the vasoproliferative tumor. Furthermore, increased expression of VEGF and CXCR4 was detected in more active hemangioblastomas. CONCLUSIONS: Surgical resection of large retinal hemangioblastomas may be useful for therapy in selected VHL patients. Activated VHL lesions produce more VEGF. This is the first demonstration of CXCR4 expression in VHL disease–associated retinal hemangioblastomas. We suggest targeting CXCR4 as an additional therapeutic strategy for VHL disease–associated retinal hemangioblastomas.